Faithfulness in Erwin, Gunn & Carrol’s Movie Script I Still Believe - Losu, Elsha Resita; Mamentu, Agustine C.; Andries, Fivy (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This research aimed to reveal how commitment and communication are revealed as parts of faithfulness were portrayed in the movie I Still Believe, which told the true story of Christian singer Jeremy Camp. Using a qualitative approach, this study analyzed commitment and communication as parts of faithfulness through the lens of Abrams' (1979) objective theory. The data, derived from the film, highlighted two key aspects of faithfulness; commitment and communication both connected to God and spouse. These elements collectively illustrated faithfulness as a deliberate choice rather than an emotional reaction. Faithfulness to God was portrayed as unwavering trust and dependence on divine guidance, even in times of suffering. Likewise, faithfulness in human relationships mirrored this devotion through patience, trust, and perseverance. The film underscored that true faithfulness was not about seeking immediate answers but about surrendering to a higher plan. Ultimately, I Still Believe demonstrated that faithfulness strengthened both spiritual and personal bonds, shaping character and resilience in the face of adversity.